Roman Provincial Coins Found in Lesser Poland: an Overview - Bodzek, Jarosław; Jellonek, Szymon; Zając, Barbara (Acta Archaeologica Lodziensia, 2019)
The aim of the present article is to summarize a current state of research on the problem of inflow of Roman provincial coins into Lesser Poland in antiquity. The term “provincial coinage” as used here refers to coins from the mints producing coinages for the purpose of provincial circulation, as well as to the so-called pseudo-autonomous and autonomous coinages struck by various local mints. We consider coins produced in mints located in the Eastern part of the Roman Empire, beginning from Dacia and Moesia, and farther east and south to the provinces of Asia Minor, Syria, and Egypt as well as these struck by the rulers of the Bosporan Kingdom. The chronological scope of this presentation is defined by the final decades of the Roman Republic/the beginning of the Roman Empire and the Diocletian’s reform (AD 294). We shall concentrate on the relevant finds of bronze coinage and the so-called billon coins. Only one brief paragraph is devoted to silver issues.